Assessing the effectiveness of climate assemblies: framework for measuring deliberative impact - Skarzauskiene, Aelita; Mačiulienė, Monika; Kovaitė, Kristina; Šūmakaris, Paulius; Kotrikla, Anna-Maria; Gulevičiūtė, Gintarė; Fameli, Kyriaki-Maria; Polydoropoulou, Amalia; Balkė, Rūta (Frontiers in Climate, 2025)
IntroductionClimate assemblies have gained attention as participatory governance instruments designed to address complex climate challenges through inclusive deliberation. However, despite their growing prominence, systematic approaches for assessing their performance and impact remain scarce. This study responds to that gap by proposing a structured evaluation framework to measure the deliberative effectiveness of climate assemblies within the broader context of democratic climate governance.MethodsAn iterative, multi-stakeholder design process guided the development of the framework. It drew upon best-practice reviews, stakeholder consultations, and collaborative workshops. The resulting structure integrates input, process, and outcome dimensions, each associated with two key objectives: policy legitimacy, rooted in inclusive and trusted participation, and policy effectiveness, reflected in the influence of assembly recommendations on climate policy. The framework was piloted in two European climate assemblies to test its applicability and robustness.ResultsThe pilot evaluations demonstrated that applying a systematic assessment framework enhanced transparency and accountability within deliberative processes. It enabled a clearer understanding of how well assemblies fulfilled their aims of inclusion, deliberative quality, and policy relevance. Findings also revealed that consistent evaluation helps identify design strengths and weaknesses, supporting more evidence-based improvements in future assemblies.DiscussionThe study shows that structured evaluation is not merely a reporting exercise but a mechanism to strengthen democratic legitimacy and practical effectiveness. By offering standardized criteria and measurable indicators, the framework assists policymakers, organizers, and researchers in assessing whether climate assemblies translate citizen participation into tangible climate action. It contributes a practical and theoretically grounded tool for advancing deliberative democratic practices in climate governance.